LAS REDES DE LA SOCIEDAD - Mires, Fernando (La Sociología en sus Escenarios, 2009)
Abstract. Most of the concepts of social sciences are metaphors that can only give imaginative account of reality, without claiming any absolutism on the so-called objective reality. However, the metaphor of the networks has the particularity to suggest relationships that are not in the simple duality society / state, as a society redificada delivers images to different categories such as "civil society" or "social actor." The appeal of the social redificación is more important in a period where the deterioration of the nation states unarmed societies leaves behind him, fought to pure means of the global market. But if the withdrawal of the state is in a society attached internally by multiple communication networks, the prospects are not only disastrous, as they want us to believe ideologists of globalisation: it is necessary to shift the gaze from the State (Marxist and neo-liberal obsession ) into space for the formation of a functional society. Resumen. La mayoría de los conceptos de las ciencias sociales son metáforas que solo pueden dar cuenta imaginativa de la realidad, sin pretender ningún absolutismo sobre la llamada realidad objetiva. Sin embargo, la metáfora de las redes tiene la particularidad de sugerir relaciones que no se encuentran en la simple dualidad sociedad/Estado, pues una sociedad redificada entrega imágenes diferentes a categorías como “sociedad civil” o “actor social”. El recurso de la redificación social es más importante en un período donde el deterioro de los Estados nacionales deja sociedades inermes detrás de sí, libradas a los puros arbitrios del mercado mundial. Pero si el retiro del Estado se realiza en una sociedad sujetada interiormente por múltiples redes comunicativas, las perspectivas no pueden ser solamente catastróficas, como quieren hacernos creer los ideólogos de la globalización: se hace necesario desplazar la mirada desde el Estado (obsesión marxista y neoliberal) hacia el espacio de la constitución orgánica de la sociedad.